Analysis and interpretation of 18 years of mercury observations since 1996 at Mace Head, Ireland. (January 2015) - Weigelt, A.; Ebinghaus, R.; Manning, A.J.; Derwent, R.G.; Simmonds, P.G.; Spain, T.G.; Jennings, S.G.; Slemr, F.
Abstract: Observations of atmospheric mercury at the Mace Head Atmospheric Research Station on the Atlantic coast of Ireland made from February 1996 to December 2013 are analyzed. Using meteorological analysis and a sophisticated Lagrangian dispersion model, the hourly averaged mercury concentrations were attributed to four different air mass types: baseline, local, European polluted, and sub-tropical maritime. Monthly median Hg concentrations of all types decreased over the analyzed period but the trend for sub-tropical maritime air masses was with −0.016 ± 0.002 ng m −3 yr −1 in absolute terms significantly smaller than the trends for all other classes which varied between −0.021 and −0.023 ng m −3 yr −1 . The seasonal variation for sub-tropical maritime air masses is also shallower than for all other classes. This is most likely due to shallower seasonal variation of oxidant concentrations at lower latitudes. The north-south gradient of the trend is qualitatively consistent with the GEOS-Chem model predictions based on decrease of mercury concentrations in surface waters of the North Atlantic but the trends are smaller than predicted. Tests for temporal change of the trends indicate that the decreasing trends of mercury concentrations are leveling off for all air masses with possible exception of the sub-tropical maritime air mass. Quantitative assessment of the trend changes, however, will require a longer time series of the mercury measurements at Mace Head. Highlights: World's second longest time series of atmospheric mercury at Mace Head analyzed. Air mass separation: baseline, local, European polluted, and sub-tropical maritime. Decreasing trend in sub-tropical maritime air is smaller than for other classes. North-south trend gradient is consistent with GEOS-Chem model prediction. Decreasing trends for baseline, European polluted and local air are leveling off.